Potassium phosphite combined with reduced doses of fungicides provides efficient protection against potato late blight in large-scale field trials. (August 2016) - Liljeroth, Erland; Lankinen, Åsa; Wiik, Lars; Burra, Dharani Dhar; Alexandersson, Erik; Andreasson, Erik
Abstract: Potato late blight caused by the oomycete Phytophthora infestans is a devastating disease of potato worldwide. Most of the potato cultivars grown in conventional agriculture are susceptible, or at best moderately resistant, and require frequent applications of fungicides to avoid heavy yield losses. In field trials spanning four years, we have investigated the effect of potassium phosphite, an inorganic salt on potato late blight. Potassium phosphite is known to induce defence responses in potato and to also have direct toxic effects on oomycetes, which in turn counteract late blight and tuber blight development. However, the use of this salt is not yet implemented and approved in European potato cultivation. We compared the effect of phosphite alone with fungicides currently used in Swedish potato cultivation. We also investigated the combined use of potassium phosphite and reduced doses of fungicides. Table potato cultivars and starch potato cultivars with different levels of resistance were used. We found that potassium phosphite in combination with reduced doses of fungicides results in the same level of protection as treatments with the recommended full dose of fungicides. These combined treatments reduce the need of traditional fungicides and may also decrease the selection pressure for fungicide resistance development in the pathogen. In relatively resistant starch potato cultivars using phosphite alone gave sufficient protection against late blight. Furthermore, in starch potato a combination of phosphite and fungicides at two-week intervals provided similar protection to weekly applications of fungicide at the recommended dose. Foliar treatment with phosphite also gave protection against tuber blight at similar levels to that of the best-performing fungicide. Our data suggests that potassium phosphite could be used in potato cultivation in temperate regions such as in Sweden, at least in combinations with reduced rates of fungicides. The implementation of the use of phosphite in practical potato crop protection as part of an IPM strategy is discussed. Doses, intervals and combinations could be adjusted to the level of cultivar resistance. Highlights: Potassium phosphite provided protection against potato late blight in field trials. In relative resistant starch potato phosphite performed as good as fungicides. A mixture of phosphite and half dose fungicide gave good protection. Potassium phosphite protected against tuber blight as well as the best fungicide. Potassium phosphite may be integrated into late blight control strategies.